Beyond Carceral Responses: Intimate Partner Violence and the Structural Realities of Rural Nigeria - ADEOYE, Beatrice Damilola; BAMIDELE, Titilayo Lydia; BAKENNE, Nureni Aremu; BAMIDELE, Seun (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Intimate Partner Violence (IPV) remains pervasive in rural Nigeria, despite the existence of national legislation such as the Violence Against Persons Prohibition Act and Nigeria’s ratification of international treaties aimed at eliminating gender-based violence. Although research has explored the general patterns of gender-based violence, limited scholarly and policy attention has been given to the structural and spatial dynamics sustaining IPV in rural contexts. This article foregrounds critical perspectives informed by abolition feminism to advance a framework for understanding the embeddedness of IPV within Nigeria’s rural socio-political fabric. We examine how histories of patriarchal control, state neglect, and familial structures produce and sustain IPV as a normalized condition of rural life. We also explore how carceral approaches to justice often fail to account for the lived realities of rural women, reinforcing cycles of silence, impunity, and harm. We argue that abolition feminist frameworks are essential for addressing the gendered and systemic nature of IPV in rural Nigeria, and for envisioning transformative alternatives rooted in community, care, and structural change.